Penyelidikan Kampas Rem Komposit Matriks Aluminium Diperkuat Boiler-Fly-Ash dan Silika Terhadap Nilai Densitas dan Kekerasannya - Akhmad Hasyim Fikri; Sukanto Wiryono; M Subhan (P3M Politeknik Negeri Cilacap, 2025)
This study aims to investigate the effect of the percentage of reinforcement and hot compaction pressure on the density value of Aluminum Matrix Composite brake pads, reinforced with Boiler-Fly-Ash and silica sand. The Powder Metallurgy method was used in this study, with variations in the weight fraction of reinforcement being 6%, 10%, and 14%. Mixing of the matrix powder and reinforcement was performed using a Ball Mill Machine, with a Ball Powder weight Ratio of 10:1, within 6 hours of mechanical alloying at a speed of 90 rpm. The molding process used a hot compaction system in the form of a Hydraulic Jack machine with an upper press and a lower press, with a hot pressing temperature of 350 ºC, a holding time of 10 minutes, at a pressure variation of 5200 Psi, 5600 Psi, and 6000 Psi. The sintering process used a temperature of 600 ºC at a holding temperature of 10 minutes. The density test of the specimen uses the ASTM B962-17 standard with the Archimedes theory approach, while the hardness test uses the Brinnel Hardness, referring to ASTM E110-14. The result, the highest average density value is 2.10 g/cm³ with a reinforcement percentage variation of 10%, while the lowest density value is 1.90 g/cm³ with a reinforcement percentage of 14%. The highest hardness value is 42.93 HB with a percentage of 10%, while the lowest hardness value is 41.4 HB with a reinforcement percentage of 14% compaction of 6000 Psi